2007
DOI: 10.1074/jbc.m704672200
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of NEIL2-mediated Oxidized Base Excision Repair via YB-1 Interaction during Oxidative Stress

Abstract: The recently characterized enzyme NEIL2 (Nei-like-2), one of the four oxidized base-specific DNA glycosylases (OGG1, NTH1, NEIL1, and NEIL2) in mammalian cells, has poor base excision activity from duplex DNA. To test the possibility that one or more proteins modulate its activity in vivo, we performed mass spectrometric analysis of the NEIL2 immunocomplex and identified Y box-binding (YB-1) protein as a stably interacting partner of NEIL2. We show here that YB-1 not only interacts physically with NEIL2, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 52 publications
(24 reference statements)
2
104
0
2
Order By: Relevance
“…For example, we have shown ROS-mediated activation of NEIL1 and APE1 [183,184]. We have shown that ROS enhances NEIL2 complex formation [161]. ROS also enhances modification of OGG1 [180] and possibly other BER proteins.…”
Section: Summary and Future Perspectivesmentioning
confidence: 88%
See 2 more Smart Citations
“…For example, we have shown ROS-mediated activation of NEIL1 and APE1 [183,184]. We have shown that ROS enhances NEIL2 complex formation [161]. ROS also enhances modification of OGG1 [180] and possibly other BER proteins.…”
Section: Summary and Future Perspectivesmentioning
confidence: 88%
“…Formation of the multiprotein complexes for oxidative damage repair is enhanced by ROS [51,161]. It was previously shown that NEILs carry out SN-BER mediated by PNK, Pol β, Lig IIIα and XRCC1 by stably interacting with Pol β, Lig IIIα and XRCC1 [51,115].…”
Section: Repair Interactome -A New Paradigm In Bermentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the common perception that the repair of oxidatively damaged bases in DNA via the BER pathway involves only a few conserved repair proteins, a more complex picture of BER is now emerging in that BER comprises several alternative subpathways that utilize distinct sets of repair enzymes and other proteins (16,19,21,35,46). We have been exploring the role of noncanonical proteins in oxidized base repair and have characterized the proteins present in immunoprecipitates of early BER enzymes including DGs.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, several noncanonical factors have been demonstrated to participate BER, even though their in vivo functions are yet to be fully unraveled. The list of non-BER proteins includes for instance: YB-1 [which has been shown to interact with the endonuclease VIII-like 2 (NEIL2) glycosylase (35), the endonuclease III-like glycosylase (NTH1) and APE1 (29)], NEIL2 [which was also found to interact with the RNA-binding protein hnRNP-U (6)], HMGB1 [which has been implicated in single-strand break (SSB) repair involving Polb (90)] and the tumor suppressor p53, which was also shown to play a role in DNA damage repair through direct binding to APE1 and Polb (168). The list of these non-BER proteins is still growing, supporting the notion that BER in vivo is far more complex than the simple model that we can reconstitute in vitro.…”
Section: Relevance Of the Unfolded Domains In Ber Proteinsmentioning
confidence: 99%